Rank-order weighting of web attributes for website evaluation - Saeid, Mehri; Abd Ghani, Abdul Azim; Selamat, Mohd Hasan (Zarqa University, 2011)
The rapid growth of web applications increases the need to evaluate web applications objectively. In the past few years some valuable works like WebQEM tried to objectively evaluate the web applications. However, still weighting web attributes which is one step of evaluation of web applications is completely subjective, depending mostly on experts’judgments. In this paper a two,step weighting approach is proposed. The approach divided the weighting step into two steps which are ranking and then weighting by using rank,order weighting formula. A simulation was conducted to compare using different rank,order weighting methods (RR, RS, and ROC) with the TRUE weights (simulated experts’ judgments without prior ranking). Two kinds of comparison were done; comparison on weights and comparison on quality scores. From the results, using Rank,Sum is suggested as a good surrogate for experts’ weights for the attributes when evaluating some web applications.